Application of the Clarke and Wright Savings Algorithm to Solve the Vehicle Routing Problem in Optimizing Chip Distribution - Sitompul, Apri Yani; Husein, Ismail (KUBIK: Jurnal Publikasi Ilmiah Matematika, 2025)
Efficiency in the distribution process is crucial for companies to reduce operational costs while maintaining service satisfaction. This research aims to optimize the product delivery route for the Keripik Cinta Mas Hendro business by applying the Clarke and Wright Savings algorithm approach to solve the Vehicle Routing Problem (VRP). This method works by calculating the distance savings from combining distribution points, then constructing optimal routes based on the order of highest savings while still considering vehicle capacity. The data used consists of customer coordinates, which are processed into distances between locations using the Euclidean formula. The results show that the distribution route, which was initially divided into three lanes with a total length of 403.54 km, can be simplified into two lanes with a total length of 272 km. This study proves that the Clarke and Wright Savings algorithm is able to provide a more cost-effective distribution solution. Keywords: Distribution, Optimization, Chips, VRP, Clarke and Wright Savings MSC2020: 90B06, 68W40, 90C59 Abstrak Efisiensi dalam proses distribusi sangat penting bagi perusahaan agar dapat menekan biaya operasional sekaligus menjaga kepuasan pelayan. Penelitian ini bertujuan untuk mengoptimalkan jalur pengiriman produk keripik pada usaha Keripik Cinta Mas Hendro dengan menerapkan pendekatan algoritma Clarke and Wright Savings dalam menyelesaikan permasalahan Vehicle Routing Problem (VRP). Metode ini bekerja dengan menghitung nilai penghematan jarak dari penggabungan titik-titik distribusi, lalu menyusun rute optimal berdasarkan urutan penghematan tertinggi yang tetap memperhatikan kapasitas kendaraan. Data yang digunakan berupa koordinat pelanggan yang diolah menjadi jarak antar lokasi menggunakan rumus euclidean. Hasil menunjukkan bahwa rute distribusi yang semula terbagi tiga jalur dengan total 403,54 km dapat disederhanakan menjadi dua jalur dengan total 272 km. Penelitian ini membuktikan bahwa algoritma Clarke and Wright Savings mampu memberikan solusi distribusi yang lebih hemat. Kata kunci: Distribusi, Optimasi, Keripik, VRP, Clarke and Wright Savings MSC2020: 90B06, 68W40, 90C59